The Business of Development: Trends in Lending by Multilateral Development Banks to Latin America, 1980-2009 - Katharina Michaelowa; Chris Humphrey (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
In this paper we investigate how country shareholding arrangements affect the lending of multilateral development banks (MDBs) under different economic conditions and over time. To do so, we consider three different types of MDBs - one dominated by non-borrowers (the World Bank), another controlled by borrowing countries (the Corporación Andina de Fomento, CAF), and a third where control is more evenly split between borrowers and non-borrowers (the Inter-American Development Bank, IADB) - and a common set of borrowing countries in Latin America. Descriptive statistics as well as econometric analysis based on seemingly unrelated regression estimation (SURE) and panel regressions indicate that the lending of the three MDBs does indeed react in a systematically different way to specific economic conditions. As a general trend, countries increasingly favor the CAF and IADB as a source of multilateral borrowing, while during crisis times World Bank lending tends to increase significantly and more strongly than lending by the CAF. IADB lending also increases very strongly during crises, but remains at a relatively high level throughout. In line with expectations based on the different shareholder arrangements, the paper also finds links between borrower government policy stances and World Bank/IADB lending, but none for the CAF.
Keywords: 330